Narasi Gender dan Pemberdayaan Perempuan dalam Laman Digital Let’s Read: Kajian pada Cerita-cerita dari Indonesia - Maylani, Isna (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The limitations of learning media that are gender-responsive and not gender biased are one of the obstacles to achieving gender equality in the world of education. Meanwhile, the presence of the Lets' Read digital page is a digital-based learning media that is often used to improve literacy and reading skills, but has not been optimally utilized in promoting gender equality issues. This research tries to explore how Let's Read digital media captures gender narratives and women's empowerment through stories set in Indonesia. The method used is qualitative descriptive. The method used in data collection is observation through strict reading, either literary texts that are used as research objects as primary data or other texts that come from journals and supporting books in accordance with the formal object of research as secondary data sources. Data analysis uses descriptive and explanatory approaches. The results of the study showed that the 12 story titles contained diverse gender narratives with multicultural story contexts. In addition, the stories set in postcolonial culture also show the tendency of women to support each other so that a strong empowerment discourse is realized through the diversity of professions.